Couching Resistance : Women, Film, and Psychoanalytic Psychiatry - Walker, Janet (Book collections on Project MUSE., 1993)
Explores how American psychoanalytic psychiatry and Hollywood cinema between World War II and the mid-1960s negotiated womens psychosexuality and life experience.